Study of Limestones from the Nfayil Formation in Bahr Al-Najaf Depression and Suitability for Thermal conductivity - Ahmed , Hussien Ghni; Issa, Murtadha Jabbar; Ali , Jaffar Hussain (Iraqi Journal of Science, 2022)
The evaluation of the Nfayil limestones in Bahr Al-Najaf Depression as construction materials was done on 15 sites distributed over a region. The study included field and laboratory aspects. The field side included collecting information about the study area and samples. As for the laboratory side, laboratory tests were conducted to study the thermal conductivity of samples by a device called Lee’s disc in the Tikri University. The thermal conductivity results ranged between 2.34 and 0.27. The rocks are of high thermal insulation at low temperatures and low insulation at high temperatures according to the specifications of the suitability of limestone for thermal conductivity standards (ASTM C 1057-03-2010).